Aplikasi Metode Full Costing Dalam Penentuan BEP Pada Produk Diversifikasi Moringa - Eny Idayati, eny_Idayati; Setiawan, Krisna; Kartiwan (JURNAL AGRICA, 2024)
Pricing food products from Moringa diversification that are appropriate and competitive is one of the basics in an effort to increase competitiveness and profits for local processed food producers. In this case, the full costing method can be one of the tools to set the optimal price. The research was conducted at TEFA Indi. Eat&Co. Kupang State Agricultural Polytechnic, with the aim of analyzing the application of the full costing method in determining the cost of production of Moringa diversification, and evaluating the effectiveness of the full costing method on 3 products, namely Moringa Leaf Teabags, Dried Moringa Noodles, and Moringa Seed Snack Bars. The research method used is full coastng by calculating the total costs incurred during the production of Moringa products including the cost of main ingredients, auxiliary materials, labor costs, and overhead costs. The results showed that the cost of goods for Moringa Leaf Teabag, Dried Moringa Noodles, and Moringa Seed Snack Bar products were Rp. 33,992,736, Rp. 7,173,845, and Rp. 11,036,604. The full costing method has an effective impact in determining production costs comprehensively on Moringa diversified products in accordance with accounting principles so that it can provide information for long-term decision making related to pricing, product evaluation, and optimization of further production planning.